Ten lectures on natural semantic metalanguage : exploring language, thought and culture using simple, translatable words - Goddard, Cliff (Distinguished lectures in cognitive linguistics., 2018)
This lively lecture series by a leading expert introduces the theory, practice and application of a versatile, rigorous and well-developed approach to cross-linguistic semantics: the NSM approach originated by Anna Wierzbicka. Topics include: history and philosophy of the study of meaning, semantic primes and molecules, emotions, evaluation, verbs and event structure, cultural key words and scripts. Case studies come from English, Chinese, Danish, and other languages. Applications in language teaching and intercultural education are also covered, along with comparisons between NSM and other leading approaches to linguistic semantics. The book will appeal to students and scholars of linguistics at all levels, communication and translation scholars, and anyone interested in a systematic and non Anglocentric approach to meaning, culture and cognition.